A new 360° rotating type stimuli for improved SSVEP based brain computer interface. (March 2020) - Bisht, Anupam; Srivastava, Shivam; Purushothaman, Geethanjali
Highlights: Development of 360° Rotating Type Stimuli for Brain Computer Interface. Design of Rotating type stimuli at different speeds. Identification of approiate stimuli to improve BCI with information transfer rate and accuracy. Identification of appropriate channel/channel combination to improve BCI with information transfer rate and accuracy using CCA and PSDA. Abstract: The authors investigated for first time clockwise and counter clockwise 360° rotating stimuli at two different speeds of rotation/phase for brain computer interface (BCI). The 360° rotating stimuli of frequencies 3 Hz, 7.5 Hz and 10 Hz are considered and compared to the performance with non-rotating flickering stimuli using signal-to-noise ratio at four channels Oz, Pz, O1 and O2 . In addition, the authors have also attempted to study the effect of stimuli in varying combinations of four channels in discriminating stimuli frequencies. This paper investigated the discrimination of stimuli frequencies using power spectral density analysis (PSDA) and canonical correlation analysis (CCA) with information transfer rate (ITR). The results revealed the maximum average classification accuracy of 87.6 % is achieved from the single channel Oz, for clockwise rotating slow (CS) stimuli using CCA. The maximum average accuracy of 90.6 % is achieved from the channel combinations Oz, Pz, and O1 for CS rotating stimulus from CCA. It is noticed that, counter clockwise fast rotating stimulus is poor performing in single channel performance analysis. However, counter clockwise fast rotating stimulus has shown maximum average accuracy of 90 % considering all four channels with CCA. The maximum average ITR of 58.5 bit/min is achieved using signals of CS stimuli from the Oz channel and 65.1 bit/min is achieved with multichannel combination of Oz, Pz, O1 for clockwise slow rotating stimuli. The results indicate an enhancement in performance of SSVEP based BCI with clockwise rotating stimuli and may be considered for communication and or control applications.